1997
DOI: 10.1016/s0005-2728(96)00155-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and viscosity dependence of the electron-transfer reaction between plastocyanin and cytochrome c labeled with a ruthenium(II) bipyridine complex

Abstract: The temperature and viscosity dependence of the photo-induced electron-transfer reaction between plastocyanin and cytochrome c labeled at Lys13 with Ru(4,4'-dicarboxybipyridine)(bipyridine)(2+)2 have been investigated. In these studies, a short pulse of 450 nm light was used to excite the ruthenium complex which was oxidatively quenched by the iron center of cytochrome c. The resulting Fe(II) cytochrome c was then rapidly reoxidized by plastocyanin. The reactions were investigated over a temperature range of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The value for the protein friction (σ ) 4.0 cP) is comparable to the values measured for the ZnCc-plastocyanin and ZnCc-cytochrome b 5 complexes (3)(4)(5). The activation parameters (∆H q ) 22.6 ( 1.4 kJ/mol and ∆S q ) -76 ( 5 J mol -1 K -1 ) obtained from the temperature dependence of k 4 are also consistent with gating by protein-protein reorientation (4)(5)(6). Fitting the temperature dependence of k 4 with the Marcus equation (eq 3) gives a reorganization energy λ of 1.9 eV, which is much larger than the value of 0.5-0.9 eV predicted for the elementary electron transfer step in this system (22).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The value for the protein friction (σ ) 4.0 cP) is comparable to the values measured for the ZnCc-plastocyanin and ZnCc-cytochrome b 5 complexes (3)(4)(5). The activation parameters (∆H q ) 22.6 ( 1.4 kJ/mol and ∆S q ) -76 ( 5 J mol -1 K -1 ) obtained from the temperature dependence of k 4 are also consistent with gating by protein-protein reorientation (4)(5)(6). Fitting the temperature dependence of k 4 with the Marcus equation (eq 3) gives a reorganization energy λ of 1.9 eV, which is much larger than the value of 0.5-0.9 eV predicted for the elementary electron transfer step in this system (22).…”
Section: Discussionsupporting
confidence: 81%
“…These observations suggest that k eta is not controlled by configurational gating, but may represent the elementary electron transfer event. Previously examined systems in which electron transfer is limited by configurational gating are characterized by a large dependence of the rate constant on viscosity and temperature ( ).…”
Section: Discussionmentioning
confidence: 99%
“…The high and increasing resin viscosities affect the behavior of the chemical reactions occurring within them. , For instance, in a previous study we found that the high viscosity of the reaction media changed the trend of the ET reactions in thiol–ene polymerization resins by affecting reorganization energies of thiol monomers . Several other studies have also observed viscosity-dependent effects on chemical reactivity. …”
Section: Resultsmentioning
confidence: 84%
“…The isokinetic correlation, which holds well for the aforementioned unimolecular reactions, does not apply to the redox reaction between ferrocytochrome c and cupriplastocyanin. Activation parameters ∆H q and ∆S q were reported in studies in which this reaction was induced by mixing (39) and by intramolecular reduction of ferricytochrome c by a ruthenium(II) complex attached to the surface of this protein (98). The former reaction, between the native proteins, is certainly bimolecular.…”
Section: Choice Of Mutations Is Guided By Previous Experimentsmentioning
confidence: 99%